Comprendre la production et la régulation des conflits environnementaux pour caractériser une trajectoire de sécurisation du risque - Yvan Renou; Antoine Brochet; Jean-Dominique Creutin (Revue de la Régulation)
This paper deals with the historical evolution of flood prevention institutions in the plain surrounding Grenoble, from 1219 to 1789. Based on an analysis of the existing scientific literature, we map the evolving relationship between the inhabitants and the public authorities to cope with flooding. For this purpose, we use the notion of hydro-social contract. We elaborate a grid based on historical institutionalism in order to examine the quality of the institutions coping with flood risk over time. Meanwhile we follow a critical approach in the sense that we look at flooding as an indicator of environmental inequalities. Our results enable the identification of three periods of time, each with its own way of providing the population with flood protection. We show a gradual transfer of responsibility for flood intervention, which moved from the feudal communities through to the city of Grenoble and finally to the central State. In terms of institutional arrangements, we highlight the changing structure of these institutions over time and also across the cognitive, normative and regulative stages. This paper presents finally the advent of a complex institutional regime that resulted in major freedom limitations to both the population and the rivers.